The correlation between nutritional status and diet quality with acute respiratory infections in preschool children aged 5 to 7 years - Melika Melunović; Belma Krdžalić-Zečević; Mirela Lisičić-Konaković; Amela Kulašević; Lejla Kurtalić (Medicinski glasnik, 2024)
Aim: To investigate the relationship between nutritional status (NS) and diet quality (DQ) with the frequency of acute respiratory infections (ARIs) in children aged 5 to 7 years. Methods: Data were obtained through questionnaires. Anthropometric measurement, correlations between body mass index (BMI) and DQ with frequency of ARIs were analysed. Results: A total of 129 children with an average age of 72.2±4.2 months were examined. Mal-nourished children had a 3.4 times higher probability of ARIs (OR=3.449; p=0.025, 95% CI=0.109-29.049) and a 5.6 times higher probability of bronchopneumonia compared to those with normal weight (OR=5.643; p=0.049, 95% CI=0.874-36.434). There was a significant positive association between the consumption of meat and meat products with bronchitis (p=0.030; OR 9.921; 95% CI -1.252, +78.610) and a significant negative relationship between the consumption of cooked meals and ARIs in total (p=0.015; OR 0.046; 95% CI -0.004, +0.552). Unexpectedly, a significant positive association was found between the consumption of fresh fruits and vegetables and some respiratory infections, which needs to be verified with additional analyses. Conclusion: DQ and NS are associated with the frequency of ARIs in preschool children. Additional analyses are needed with a larger number of participants in order to form more precise conclusions.
Keywords: child; diet; nutri-tional status; pre-school; respiratory tract infections